Anti-tick vaccine candidate subolesin is important for blood feeding and innate immune gene expression in soft ticks. - Krittika Nandy; Comfort Tamakloe; Daniel E Sonenshine; Hameeda Sultana; Girish Neelakanta (Public Library of Science (PLoS), 2023)
Subolesin is a conserved molecule in both hard and soft ticks and is considered as an effective candidate molecule for the development of anti-tick vaccine. Previous studies have reported the role of subolesin in blood feeding, reproduction, development, and gene expression in hard ticks. However, studies addressing the role of subolesin in soft ticks are limited. In this study, we report that subolesin is not only important in soft tick Ornithodoros turicata americanus blood feeding but also in the regulation of innate immune gene expression in these ticks. We identified and characterized several putative innate immune genes including Toll, Lysozyme precursor (Lp), fibrinogen-domain containing protein (FDP), cystatin and ML-domain containing protein (MLD) in O. turicata americanus ticks. Quantitative real-time polymerase chain reaction analysis revealed the expression of these genes in both O. turicata americanus salivary glands and midgut and in all developmental stages of these soft ticks. Significantly increased expression of fdp was noted in salivary glands and midgut upon O. turicata americanus blood feeding. Furthermore, RNAi-mediated knockdown of O. turicata americanus subolesin expression affected blood feeding and innate immune gene expression in these ticks. Significant downregulation of toll, lp, fdp, cystatin, and mld transcripts was evident in sub-dsRNA-treated ticks when compared to the levels noted in mock-dsRNA-treated control. Collectively, our study not only reports identification and characterization of various innate immune genes in O. turicata americanus ticks but also provides evidence on the role of subolesin in blood feeding and innate immune gene expression in these medically important ticks.